THE INTERPLAY OF TEACHERS’ BELIEFS, ATTITUDES, AND THE IMPLEMENTATION OF DIFFERENTIATED INSTRUCTION IN INDONESIAN EFL CONTEXTS - Nirwanto Maruf (English Review: Journal of English Education, 2023)
The aims of this study were to examine the relationship between teachers’ beliefs and attitudes about differentiation and the implementation of this approach in English as Foreign Language (EFL) classrooms in Indonesia. The study also aimed to examine the impact of these practices on student engagement and motivation. A total of 100 teachers from several different schools participated in the study which were scattered from the major islands in Indonesia, and the data were collected using a self-report questionnaire that was administered online by provided with link. Correlations analysis were conducted to examine the relationships between the variables. The results showed that teachers’ beliefs and attitudes about differentiation had a strong positive correlation with the implementation of this approach in their classrooms (r = 0.75, p < 0.001). in addition, professional development in differentiation was positively correlated with teachers’ beliefs and attitudes about this approach (r = 0.65, p < 0.001). The results also indicated a strong positive relationship between teachers’ beliefs and attitudes about differentiation and student achievement in EFL classrooms (r = 0.80, p < 0.001). These findings suggest that teachers’ beliefs and attitudes about differentiation play a significant role in their implementation of this approach in the classroom, and that differentiated instruction has the potential to improve student achievement and engagement in EFL classroom in Indonesia. However, further research with a larger and more diverse sample is needed to fully understand these relationships in the Indonesian context.